The Conjunctions "Sebab" and "Karena" in the Minangkabau Language Variety: A Corpus-Based Syntactic Study - Lubis, Muhammad Afdhaluz Zikri; Sinar, T. Silvana; Prihantoro (International Journal Linguistics of Sumatra and Malay, 2024)
This study aims to analyze the frequency, colligation pattern, and syntactic role of "karena" and "sebab" conjunctions in the MinangKabau language variety. The Minang LCC corpus of the Corpus Query Processor (CQPweb) gadget was used to obtain data. There are two phases of analysis in this research: quantitative analysis and qualitative analysis. The frequency of cause and because conjunctions in the Minang-Kabau language variation is ascertained by quantitative study. In the Minang-Kabau language variety, the syntactic function of cause and because conjunctions are discussed, and the colligation pattern is ascertained through qualitative analysis. The study's findings indicate that although the conjunction because occurs 37 times, the conjunction because only occurs 27 times. This shows that the conjunction karena is more often used in the Minangkabau language variety than the conjunction sebab. There are variations in the colligation patterns of the MinangKabau conjunctions sebab and karena. The conjunction sebab is followed by syntactic categories of nonpersona nominal phrases, nonpersona nouns, persona nominal phrases, verb phrases, and verbs. The conjunction karena is also followed by the syntactic categories nonpersona nominal phrase, nonpersona noun, persona nominal phrase, verb phrase, and verb. Cause conjunctions followed by nouns, nominal phrases, verbs and verb phrases have the syntactic roles of quantity, cause, place, doer, and quality. Unlike the cause conjunction, the syntactic role of the conjunction because in the Minangkabau language variety is more. Prepositions to have syntactic roles of time, quantity, cause, place, actor, quality, and resistance.